Mismatch Between Specific and Genetic Diversity in an Evergreen Broadleaf Forest in Southeast China: A Study Case of 10.24 ha Forest Dynamics Plot of Huangshan - Xie, Lei; Chen, ShuiFei; Feng, YueYao; Li, Yao; Wang, Lu; He, LiHeng; Huang, LiQun; Wu, Jun; Guo, Ke; Ding, Hui; Fang, YanMing (Frontiers in Plant Science, 2022)
For a long time, forestry management has often focused on the protection of species diversity, and mistakenly believed that protecting species diversity protects genetic diversity. Therefore, research that integrates community ecology and population genetics has become important because it can help elucidate whether the targets for protecting specific and genetic diversity are congruent. In this study, we have emphasized the impact of the community on the population because no previous studies have considered the community composition of a place a priori. Based on the Huang Shan 10.24 ha dynamic forest plot, we a priori considered the community composition in the plot to test species-genetic diversity among the tree layers. Firstly, a redundancy analysis (RDA) found that Castanopsis eyrei and Pinus massoniana were the dominant species. Secondly, specific and genetic diversity are not congruent in Huang Shan. Finally, the structural equation model (SEM) showed that the different degrees of response by community composition and population structure to environmental heterogeneity are the main reasons for the mismatch between species diversity and genetic diversity The results suggest that we must focus on genetic diversity, as well as on protecting species diversity.